Zonas francas como mecanismo de incentivo para la inversión en el Ecuador - Arcos García, Yamile Carlota (2009)
The present thesis is based on the study choosing a Free Zone as an option to get foreign investments in Ecuador. The purpose of this paper is to determine this special regime represents potential advantages in the commercial and socioeconomic field for the country, and the tax sacrifice generated in these especial treatment zones would be compensated with the profits caused by them. All of this looking for increasing the number of investors to promote the development of the nation. This research emphasizes basic concepts and general information about Free Zones, to identify the Free Zones in Ecuador and concluding with the problems and possible solutions to improve the use of the frank regime.